Safety and Effectiveness of Total Thyroidectomy for Benign Multinodular Goitre - Musbah, Naser; Saad, Hasan I. Fadel; Mohamed, Salma Saleh (Al-Mukhtar Journal of Sciences, 2019)
Total thyroidectomy is considered the best choice for thyroids carcinoma. However, it is still controversial for benign thyroid diseases because of higher complication rates. But meticulous surgical techniques by expert surgeons can avoid most of the complications and thereby avoid the risk of reoperation for any recurrences. The objective of the study was to evaluate and justify the use of total thyroidectomy in benign thyroid diseases especially in multinodular goiter and Grave’s disease. We have carried out an ongoing prospective study of thyroidectomy cases for different indications over a span of 5 years, from 2012 to 2016; in the Surgery department, Al-Thowra teaching hospital, Al-Beida. The total number of operated cases was 353. Cases were distributed according to age, sex, diagnosis and operative procedures. Various complications encountered were enlisted. Total thyroidectomy was performed in 247 cases for MNG and Thyroid malignancy. Hemi-thyroidectomy or lobectomy was done in 82 cases for solitary nodules. Enucleation of cysts was done in 6 cases. Operations were done for recurrent nodules in 18 cases. Overall complications were few and only minor. We recommend total thyroidectomy for all cases of MNG; which will reduce the risk of recurrence and development of malignancy in residual thyroid tissue. It also can prevent secondary thyrotoxicosis.